The Effect of Asset Structure, Company Size, and Sales Growth on Capital Structure in Industrial Sector Companies on the Indonesia Stock Exchange 2021-2024 Period - OKTAVIANI, Oktaviani; MAKHSUN, Arif; PUSPITASARI, Endah Yuni (PT Keberlanjutan Strategis Indonesia, 2025)
This study analyzes the influence of asset structure, firm size, and sales growth on the capital structure of industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The research background is based on post-pandemic economic dynamics that influence corporate financing decisions and capital structure optimization based on the pecking order theory. The main objective is to examine the causal relationship between the variables of asset structure, firm size, and sales growth. Secondary data were obtained from annual financial reports, selected through purposive sampling with the criteria of industrial sector companies listed on the IDX, companies that consistently publish financial reports, companies that experience profits, and companies with positive equity, resulting in a sample of 92 samples over four years, 2021-2024. Data analysis used a descriptive approach to describe the distribution of variables, and multiple linear regression to test the hypothesis using SPSS 26 software. The results indicate that asset structure, firm size, and sales growth have a partial effect on capital structure. Simultaneously, the three variables explained 65.1% of the variation in capital structure (Adjusted R²=0.651), while 34.9% was influenced by other variables outside this study. This finding implies the need for adaptive financing strategies to address factors influencing capital structure to improve capital efficiency in the Indonesian industrial sector.